2016
DOI: 10.1111/ped.12901
|View full text |Cite
|
Sign up to set email alerts
|

Bubbly and cystic appearance in chronic lung disease: Is this diagnosed as Wilson–Mikity syndrome?

Abstract: Wilson-Mikity syndrome (WMS) was first reported in 1960 by Wilson and Mikity. They described preterm infants who developed areas of cystic emphysema in the first month of life with subsequent progression to chronic lung disease (CLD) of infancy, although these infants did not exhibit early respiratory distress, such as respiratory distress syndrome (RDS). This condition was widely accepted over the next 20 years, but WMS is now rarely mentioned and is commonly considered an anachronism. In Japan, CLD is classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Diagnosis based on chest radiography was made after 28 postnatal days by the neonatologists at each institution. A typical radiographic bubbly/cystic pattern is shown in Figure a; the other Japanese NICU reports also have shown the same bubbly/cystic appearance patterns . The postnatal radiographic bubbly/cystic appearance is recognized widely in all Japanese NICU.…”
Section: Methodsmentioning
confidence: 66%
See 3 more Smart Citations
“…Diagnosis based on chest radiography was made after 28 postnatal days by the neonatologists at each institution. A typical radiographic bubbly/cystic pattern is shown in Figure a; the other Japanese NICU reports also have shown the same bubbly/cystic appearance patterns . The postnatal radiographic bubbly/cystic appearance is recognized widely in all Japanese NICU.…”
Section: Methodsmentioning
confidence: 66%
“…Almost 90% of the subjects, however, were admitted to level 3 NICU, which might uphold the diagnostic value of the chest radiograph classification. Additionally, the bubbly/cystic chest radiograph pattern has been recognized widely as signifying the presence of severe BPD in Japanese NICU, and it might be relatively easy to recognize this chest radiograph pattern . Second, the chest radiograph classification did not have a scoring system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CXR appearance is classified into two findings: severe types showing a bubbly/cystic appearance (bubbly/cystic+) and mild types showing hazy shadows without a bubbly/cystic appearance (bubbly/cystic−). It was reported that the bubbly/cystic appearance on CXR is an important factor in patients with severe BPD in Japan . We showed an association between extremely preterm infants with bubbly/cystic+ BPD28 and a higher rate of home oxygen therapy in a Japanese population‐based cohort study.…”
Section: Introductionmentioning
confidence: 99%